2016
DOI: 10.1021/acs.chemmater.5b04767
|View full text |Cite
|
Sign up to set email alerts
|

N-Alkyl Interstitial Spacers and Terminal Pendants Influence the Alkaline Stability of Tetraalkylammonium Cations for Anion Exchange Membrane Fuel Cells

Abstract: Current performance targets for anion exchange membrane (AEM) fuel cells call for greater than 95% alkaline stability for 5000 h at temperatures of up to 120 °C. Using this target temperature of 120 °C, we provide an incisive 1 H nuclear magnetic resonance-based alkaline degradation method to identify the degradation products of n-alkyl spacer tetraalkylammonium cations in various AEM polymers and small molecule analogues. The operative alkaline degradation mechanisms and rates on benzyltrimethylammonium-, n-a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
78
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 120 publications
(81 citation statements)
references
References 51 publications
3
78
0
Order By: Relevance
“…Recent studies have shown that cyclic ammonium (24)(25)(26)(27) and tetraalkyl ammonium cations, specifically those with long alkyl chains (18)(19)(20)(28)(29)(30), have better alkaline stability than traditional benzyltrimethyl ammonium cations (31)(32)(33). Other cations, such as imidazolium (16,21,(34)(35)(36)(37)(38)(39)(40)(41)(42)(43), phosphonium (44)(45)(46)(47)(48)(49), and metal cations (50)(51)(52)(53)(54), have also been widely applied in various AAEMs.…”
Section: Significancementioning
confidence: 99%
“…Recent studies have shown that cyclic ammonium (24)(25)(26)(27) and tetraalkyl ammonium cations, specifically those with long alkyl chains (18)(19)(20)(28)(29)(30), have better alkaline stability than traditional benzyltrimethyl ammonium cations (31)(32)(33). Other cations, such as imidazolium (16,21,(34)(35)(36)(37)(38)(39)(40)(41)(42)(43), phosphonium (44)(45)(46)(47)(48)(49), and metal cations (50)(51)(52)(53)(54), have also been widely applied in various AAEMs.…”
Section: Significancementioning
confidence: 99%
“…[31][32][33][34][35] The technique would be equally applicable at different humidity,p otential, and temperature conditions. Equivalent AEMs (without DBPF) in either chloride or hydroxide forms were assembled in an AEM fuel cell and tested under conditions identical to those used in the in situ fluorescenceexperiments.…”
Section: In Situ Fluorescence Spectroscopy Experimentsmentioning
confidence: 99%
“…These conditions allowed the measurement of the rate of degradation at the most stringent conditions (OCV) reported by severala u- thors. [31][32][33][34][35] The technique would be equally applicable at different humidity,p otential, and temperature conditions. The resulting IEC and hydroxide ionic conductivity values are shown in Figures 6and 7.…”
Section: In Situ Fluorescence Spectroscopy Experimentsmentioning
confidence: 99%
“…The chemical and mechanical durability of AEMs are determined by the polymer main chains, functional cationic groups, and the arrangement of tether structures . In the past decade, there have been a variety of polymers with aromatic main backbone chains such as poly(phenylene oxide), poly(arylene ethers), poly(sulfone)s, and others, being used as AEM materials .…”
Section: Introductionmentioning
confidence: 99%